Se7en tips to succeed in ODL / Ts. Dr. Ratna Zuarni Ramli - Ramli, Ratna Zuarni (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2020)
Traditional education has been reformed drastically within the last couple of years. Meeting face to face in the same space is not the only way of learning anymore. It is difficult to discard the common way of conventional face to face classroom learning, but there is no need to be sceptical with learning through the internet. Here are some of the tips of conducting online distance learning (ODL).